Laparoscopic management of delayed traumatic left diaphragmatic hernia with intrathoracic kidney: A rare case report and technical aspects - Ganesh K. Shenoy; Marina Thomas; Ramesh B. Shamburao; Nawab Jan (International Journal of Abdominal Wall and Hernia Surgery)
Occult traumatic diaphragmatic hernias (DHs) are relatively rare and may present years after the trauma. Clinical presentations range from asymptomatic incidental findings on imaging to life-threatening incarceration of abdominal organs. Traumatic migration of the kidney into the thorax is a very uncommon event. We herein report a rare case of a 34-year-old male patient with a symptomatic DH secondary to a motor vehicle accident and a history of laparotomy for liver laceration 10 years back who underwent laparoscopic reduction and intraabdominal reposition of left kidney from thorax, suture repair of the defect with mesh reinforcement. Thoracoscopic visualization was performed to assess the efficiency and completeness of the repair and to rule out any iatrogenic pericardial injury after mesh fixation. The operative technique, difficulties encountered, and tips to overcome these challenges were discussed. With adequate expertise, reduction, and repositioning of migrated kidney, suture closure of the defect with mesh reinforcement is safe and feasible by laparoscopic approach.